2008
DOI: 10.1016/j.expneurol.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of paclitaxel-evoked painful peripheral neuropathy by acetyl-l-carnitine: Effects on axonal mitochondria, sensory nerve fiber terminal arbors, and cutaneous Langerhans cells

Abstract: Prophylactic treatment with acetyl-L-carnitine (ALCAR) prevents the neuropathic pain syndrome that is evoked by the chemotherapeutic agent, paclitaxel. The paclitaxel-evoked pain syndrome is associated with degeneration of the intraepidermal terminal arbors of primary afferent neurons, with the activation of cutaneous Langerhans cells, and with an increased incidence of swollen and vacuolated axonal mitochondria in A-fibers and C-fibers. Previous work suggests that ALCAR is neuroprotective in other nerve injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
132
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(151 citation statements)
references
References 58 publications
(60 reference statements)
16
132
0
2
Order By: Relevance
“…Our study revealed swollen disrupted mitochondria in the affected myleinated axons, which coincides with many investigators who suggested that mitochondrial swelling is a characteristic sign in paclitaxel axonopathy [37,38] . This could be explained by affection of Mitochondrial permeability transition pore (mPTP) which is a high conductance channel in mitochondrial inner membrane that contains different proteins including adenine nucleotide translocator (ANT), mitochondrial phosphate carrier (PiC), voltage-dependent anion channel (VDAC), and cyclophilin-D (Cyp-D).…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed swollen disrupted mitochondria in the affected myleinated axons, which coincides with many investigators who suggested that mitochondrial swelling is a characteristic sign in paclitaxel axonopathy [37,38] . This could be explained by affection of Mitochondrial permeability transition pore (mPTP) which is a high conductance channel in mitochondrial inner membrane that contains different proteins including adenine nucleotide translocator (ANT), mitochondrial phosphate carrier (PiC), voltage-dependent anion channel (VDAC), and cyclophilin-D (Cyp-D).…”
Section: Discussionsupporting
confidence: 92%
“…It was also confirmed that acetyl-L-carnitine does not affect the cytotoxicity of paclitaxel or carboplatin on ovarian cancer cells (Engle et al, 2009). In rats, acetyl-L-carnitine prevented paclitaxel-induced neuropathic pain, the swollen and vacuolated mitochondria caused by paclitaxel in C-fibers, but not in A-fibers (Jin et al, 2008). In addition, acetyl-L-carnitine decreased the spontaneous discharge of A-fibers and C-fibers, and blocked the development of the paclitaxel-evoked pain in the sural nerve of rats .…”
Section: Acetyl-l-carnitinementioning
confidence: 58%
“…Moreover, paclitaxel appears to gate the multi-molecular complex containing the voltagedependent anion channel, defined as mitochondrial permeability transition pore (mPTP) [19], thus causing a toxic calcium release from the mitochondria [20]. In accordance with this observation, calcium chelating agents are able to reverse paclitaxel-evoked pain [21], and acetyl-l-carnitine, which prevents mPTP opening [22], reduces the development of paclitaxel-induced neuropathic pain [23]. Administration of bortezomib leads to intracytoplasmatic vacuolization in dorsal root ganglia (DRG) satellite cells, probably due to mitochondrial and endoplasmic reticulum enlargement [24].…”
Section: Introductionmentioning
confidence: 87%